Collective farming in Nepal (Nepal agriculture collectives) - International Water Management Institute (International Water Management Institute, 2021)
Between 2015 and 2019, a set of farmer collectives were piloted in DSI4MTF and served as a model for a novel approach to addressing the challenges of small and fragmented holdings in the Eastern Gangetic Plains, unequal landlord-tenant relations, and severe irrigation access constraints faced by marginal and tenant farmers. The collectives approach entailed the formation of small groups of 4-10 farmers who cultivate a contiguous piece of land and collaborate in various ways in land preparation, production, and marketing. This documentary demonstrates how the collective method enables farmers to overcome technical and socio-institutional constraints to increase year-round cropping intensity using an integrated strategy that addresses both technical and socio-institutional constraints. Irrigation has been made possible with the installation of electric and solar boreholes, but critically, the cultivation of a large contiguous plot of land via the collective approach has made irrigation more practical and efficient – overcoming the challenge of fragmented holdings. Twinning the formation of collectives with the assistance of such agricultural machinery/technology, has enabled resource-poor and landless farmers to farm all year round. Furthermore, farmer collectives have comparatively improved farmers' negotiating power, allowing them to negotiate cheaper rents and defy traditional feudal responsibilities.